Rancangan Perbaikan Proses Produksi dengan Pendekatan Lean Six Sigma di CV. Guntur Malang - Garside, Annisa Kesy; Baya’sud, Faris (Performa: Media Ilmiah Teknik Industri, 2008)
This research aim to develop an improvement plan of GTR 2 pump production process at CV. Guntur Malang by incorporating Lean Six Sigma approach. Following DMAIC steps (Define-Measure-Analyse- Improve-Control), at Measure stage shows that the most affecting waste is waiting and defect . Next at Improve stage using 5 W – 1 H method resulted on improvement plan consist of (a) applying statistical based quality control system by developing control chart during GTR 2 pump test process, (b) additional training to operator, review and correct work instruction, (c) relocate material warehouse from Research and Development area and material stock pile rearrangement, and (d) applying coolent to material before drilling process.